Information and Technology-Based Policy Strategy for Monitoring and Evaluation of Government Agencies with Corruption-Free Zone/ Serving and Clean Bureaucracy Zone Status - Zaihan Harmaen Anggayudha; Jody Imam Rafsanjani (Badan Strategi Kebijakan Hukum, 2022)
The Integrity Zone Development is the government's attempt to reform its bureaucracy. It is considered successful when the work unit within the Ministry/Agency can achieve the status of Corruption Free Zone (WBK)/ Serving and Clean Bureaucracy Zone (WBBM). In order to maintain this status, the work units entitled as WBK/ WBM must maintain their quality by doing regular monitoring and evaluation. However, the monitoring and evaluation related to WBK/ WBM status in the Ministry of Law and Human Rights have not been performed optimally. Therefore, an attempt and strategy are needed to optimize the implementation of the monitoring and evaluation. This paper aims to determine the implementation and challenges of the work unit monitoring and evaluation with WBK/ WBM status within the Ministry of Law and Human Rights. The primary data were collected through interviews and library research. The result of this study shows that the monitoring and evaluation at the Ministry of Law and Human Rights has not been fully implemented. It can be optimized by considering the challenges faced by Internal Assessment Team. It is suggested to revise and prepare a regulation related to technical instruction for Integrity Zone Development at the Ministry of Law and Human Rights.